Adolescent baseball pitching technique: A detailed three-dimensional biomechanical analysis - Nissen, C. W.; Westwell, M.; Ounpuu, S.; Patel, M.; Tate, J. P.; Pierz, K.; Burns, J. P.; Bicos, J. (Medicine & Science in Sports & Exercise, 2007)
Purpose: Document the biomechanics of the pitching motion to help provide insight about the etiology of common injuries seen in adolescent baseball pitchers.